Evaluation of Donor Ankle Function after Harvesting Peroneus Longus Tendon Graft for Anterior Cruciate Ligament ReconstructionA Prospective Cohort Study - Mamata Manjari Sahu (JCDR Research and Publications Private Limited, 2021)
Introduction: Primary full thickness Peroneus Longus Tendon Graft (PLTG) for Anterior Cruciate Ligament Reconstruction (ACLR) has been used with good clinical outcome. Recently, it is designated as a promising graft option for ACLR. The effect of harvesting PLTG on donor ankle function is still not completely understood. Peroneus Longus Tendon (PLT) is thought to play a major role in proprioceptive regulation of the ankle joint. All the studies till date did cross-sectional assessments of ankle and foot function at or after 6 months that might have overlooked the timely detection of donor site morbidities. Aim: To evaluate the ankle function and compare the affected and sound limb function in subjects with an ACLR with autologous PLTG starting at an early postoperative visit upto six months. Materials and Methods: A prospective cohort study was conducted at a tertiary rehabilitation centre from March 2019 to March 2021 including the follow-up evaluation. As per the inclusion criteria, 63 participants after ACLR with PLTG were considered for assessment using the American Orthopaedic Foot and Ankle Society (AOFAS) ankle and hind foot scale and Foot and Ankle Ability Measure (FAAM) scale at 6 weeks, 3 months and 6 months post-ACLR follow-up. Comparison between sound and affected limbs was done during all follow-ups. The statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 18.0. Both FAAM and AOFAS ankle and foot scores were analysed with non parametric tests. Results: Mean age of 63 participants were 29.25 years. Median of AOFAS and FAAM score at 6 week, 3 month, and 6 month postACLR follow-ups were (88, 98 and 100) and (97.22, 98.80 and 100), respectively. Statistically significant increase in AOFAS and FAAM scores were observed at 3 month and 6 month as compared to 6 week follow-ups with p=0.001 and p-value=0.001 respectively. The group comparison between the affected and sound side functional scores at different study visits showed statistically significant greater values for the sound ankle than the affected ankle (FAAM: 6 week: p-value=0.001; 3 month: p-value=0.001; 6 month: p-value=0.001 and AOFAS p-value=0.001; p-value=0.001; p-value=0.001, respectively). Conclusion: The evaluation of functional outcomes showed gradual and linear improvement at subsequent postoperative visits and restores fully to 100% at 6 month indicating a nearnormal to normal donor ankle function following ACLR with PLTG by 6 months. The group comparison showed only marginal but significant difference between affected and sound ankle function.